A model for agricultural research - C. A. Bisschoff; A. de K. Marais; M. J. Van Reenen (South African Journal of Business Management, 1994)
In this article we report on a newly developed agricultural marketing research model. The development of such a model proves to supply future researchers the opportunity to employ this model in their research. This model enables the researcher to analyse more than one set of respondents within the same research structure, while comparative analyses could also be performed between the groups of respondents. The model consists of four stages, namely: establish relevant criteria; individual statistical analysis of the criteria; comparative analyses; and results and findings. Each of the four stages of the model is discussed according to the methodology used and the expected results of each stage. Warnings and procedural prescriptions are offered within each stage of the model, and checkpoints are also built in to ensure that a user of the model would not proceed towards the next stage if the previous stage was not executed satisfactorily. The benefit of the research model is that it supplies a structured framework which could be employed by future agricultural researchers to perform related research projects. The model could also be employed as a basis from which other researchers could alter or create their own research methodology since limited research has been conducted in the discipline of agricultural marketing research process.
Keywords: 650